Glove perforation in selected surgical procedures in a general hospital in La Habana, Cuba - Humberto Guanche Garcell; Anayka Gonzalez Valdés; Luis Gonzalez Alvarez; Gloria Fresneda Septiem; Katerine Cardenás Goulet; Yelina Matos Figueroa; Francisco Gutiérrez García (Elsevier, 2022)
Summary: Background: Surgical glove perforation constitutes a risk for the maintenance of aseptic technique and the risk of surgical site infection and occupational exposure to blood borne infections for healthcare workers. Aim: To identify the frequency of glove perforation in selected surgical procedures. Methods: A cross-sectional descriptive observational study was carried out in the surgical unit of the Joaquin Albarrán Hospital (La Habana, Cuba) during the period September-December 2019. Gloves used by surgeons in major urgent or elective surgical procedures were collected and tested for perforations. Findings: 757 gloves from 149 surgeons and 8 surgical specialties were tested and 95 (25.8%) had perforations. The highest frequencies of glove perforations were reported in vascular surgery (50.0%), proctology (37.9%), urology (28.0%) and general surgery (26.1%). The selected surgical procedures with the highest frequencies were open radical nephrectomy (87.5%), splenectomy (57.1%), open adenomectomy (55.6%), limb amputation (46.2%) and hysterectomy (41.7%). Glove perforation occurred more frequently in consultant surgeons (28.8%) than in residents (20.9%) (P = 0.021), in surgeons with more years of surgical experience (P = 0.003) and longer procedure duration (P = <0.001). Most glove perforations were identified in the left hand (64.1%), while 23.1% were in the right hand and 12.8% in both hands. 51.2% occurred in thumb and index finger. Differences in the patterns of glove perforation were observed among the different surgical procedures. Conclusions: Our findings provide insights into the risk of glove perforation during selected surgical procedures and the need for prevention strategies to reduce adverse consequences of glove perforation in patients and healthcare workers.